PENGARUH ICT SELF EFFICACY TERHADAP TECHNOPRENEURSHIP INTENTION DIMODERASI TECHNOPRENEURIAL LEARNING DAN CREATIVITY (Survei Pada Siswa SMKN di Kota Palembang) - Izza Aprilianti Wardani, - (2020)
This research aims to know the general description of ICT self efficacy, technopreneurial learning, creativity and technopreneurship intention students, the influence of ICT self efficacy against technopreneurship intention on students, how the interaction between technopreneurial learning and ICT self efficacy against technopreneurship intention students, the interaction between creativity and ICT self efficacy against technopreneurship intention students The research method used is the survey explanatory where the questionnaire as an instrument and use Linkert 1-5 scale with the technical collection of questionnaire spread over 217 SMKN students in Palembang. Tekhnik analysing data using simple the moderation regression analysis. The results showed that there was an influence of ICT self efficacy on the technopreneurship intention where the effect was positive and significant. The results of the study also showed that there is interaction between ICT self efficacy against technopreneurship intention which is in moderation technopreneurial learning and creativity. Keywords: ICT self efficacy, technopreneurial learning, creativity and technopreneurship intention.